2012
DOI: 10.3133/sir20125078
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of low flows and selected methods for estimating low-flow characteristics at partial-record and ungaged stream sites in western Washington

Abstract: Vertical coordinate information is referenced to the North American Vertical Datum of 1988 (NAVD 88). Horizontal coordinate information is referenced to the North American Datum of 1983 (NAD 83). Elevation, as used in this report, refers to distance above the vertical datum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Hydrologic theory generally holds that smaller, steeper basins with high drainage density will have a flashier hydrograph and faster recession (Curran et al 2012). Although some studies have found positive correlations between basin slope or flow 15 path gradient and baseflow (Sánchez-Murillo et al 2014, Tetzlaff et al 2009), these correlations appear to be a result of drastic differences in lithology, with steeper basins having greater water-holding capacity due to different rock or soil types than flatter basins.…”
Section: Basin Characteristics and Baseflows 20mentioning
confidence: 82%
“…Hydrologic theory generally holds that smaller, steeper basins with high drainage density will have a flashier hydrograph and faster recession (Curran et al 2012). Although some studies have found positive correlations between basin slope or flow 15 path gradient and baseflow (Sánchez-Murillo et al 2014, Tetzlaff et al 2009), these correlations appear to be a result of drastic differences in lithology, with steeper basins having greater water-holding capacity due to different rock or soil types than flatter basins.…”
Section: Basin Characteristics and Baseflows 20mentioning
confidence: 82%
“…For example, the variable infiltration capacity model applied to the Pacific Northwest in the United States had an median at‐site Nash–Sutcliffe efficiency of −4.39 for annual 7‐day low flows in 55 river primarily as a result of at‐site bias rather than stochastic error (Wenger et al, ). Groundwater discharge, in particular, can be very localized in river networks (Konrad, ), which complicates the following: (a) the parameterization of process‐based models, (b) the identification of basin characteristics that account for low‐flow variation in statistical models, and (c) the assignment of ungauged sites to regions or index stations in large, heterogeneous landscapes (Curran et al, ; Dodangeh, Soltani, Sarhadi, & Shiau, ; Ehsanzadeh & Adamowski, ; Laaha & Blӧschl, ; Nicolle et al, ; Yuan, ). Bias in time‐series modelling related to baseflow can be indicated by a single streamflow measurement at ungauged sites, providing an efficient means to improve the spatial resolution of low flows in region process models.…”
Section: Discussionmentioning
confidence: 99%
“…Annual and seasonal minimum streamflows are important benchmarks for managing in‐stream and out‐stream water uses in river basins (Kakouei, Kiesel, Kail, Pusch, & Jähnig, ; Olden et al, ; Petts, ; Richter, Baumgartner, Wigington, & Braun, ). Gross differentiation of streams with low (or no) baseflow from those with high baseflow remains a key problem for regional low‐flow estimation using either statistical or process models (Curran, Eng, & Konrad, ; Eng, Kiang, Chen, Carlisle, & Granato, ; Laaha et al, ; Laaha & Blӧschl, ; Wenger, Luce, Hamlet, Isaak, & Neville, ). Although regional models can reliably estimate flood magnitudes and mean streamflow, they typically have large relative errors for low flows (Castiglioni, Castellarin, & Montanari, ; Demirel, Booij, & Hoekstra, ; Laaha, Skøien, & Blӧschl, ; Nicolle et al, ; Pfannerstill, Guse, & Fohrer, ; Salinas et al, ; Staudinger, Stahl, Seibert, Clark, & Tallaksen, ; Tian, Booij, & Xu, ; Wenger et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers (e.g., Hisdal et al 2004;Jowett and Biggs 2006;Bradford and Heinonen 2008;Thomas et al 2019) have highlighted increased stress on aquatic, riparian, and hyporheic ecosystems during low flow due to decreased water availability and habitat quality. During these intervals, low flows help maintain longitudinal connectivity in the stream (Curran et al 2012). Changes in flow and groundwater levels due to precipitation and seasonal factors have ecological impacts on stream communities.…”
Section: Introductionmentioning
confidence: 99%